2016
DOI: 10.1097/md.0000000000004369
|View full text |Cite
|
Sign up to set email alerts
|

Does surgery for instability of the shoulder truly stabilize the glenohumeral joint?

Abstract: Despite the fact that surgery is commonly used to treat glenohumeral instability, there is no evidence that such treatment effectively corrects glenohumeral translation. The purpose of this prospective clinical study was to analyze the effect of surgical stabilization on glenohumeral translation.Glenohumeral translation was assessed in 11 patients preoperatively and 1 year postoperatively following surgical stabilization for anterior shoulder instability. Translation was measured using optical motion capture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 38 publications
0
36
0
1
Order By: Relevance
“…Furthermore, the difference between the subgroups is determined. OA proportion was calculated by merging all categories describing signs of OA (categories I, II, and III) instability and development of OA in the long term [7,36]. However, the Bankart repair, showing a wide range of 14% to 86% OA, may have a wider indication range compared to the bony augmentation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the difference between the subgroups is determined. OA proportion was calculated by merging all categories describing signs of OA (categories I, II, and III) instability and development of OA in the long term [7,36]. However, the Bankart repair, showing a wide range of 14% to 86% OA, may have a wider indication range compared to the bony augmentation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Chalmers P et al [13] through a systematic metaanalysis review concluded that there is no difference between the two techniques in relation to failure rates. Lädermann et al [14] in a prospective study, concluded that regardless of the surgical technique used, there is no evidence that such treatments effectively correct glenohumeral translation, leaving a residual microinstability that may be the cause of residual pain, persistent apprehension and arthrosis, but further studies are needed to better understand residual microinstability. Antunes JP et al [15] observed good results in patients with arthroscopic Bankart repair and recurrence rate of 7%, with a higher risk in young patients with ligament laxity, concluding that arthroscopic repair is a reliable method.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, if persistent apprehension is observed, 34 , 35 , 36 a multidisciplinary approach can be recommended. This can include (1) a “reafferentation” of the shoulder based on a neuromuscular and proprioceptive work, 37 (2) a neurofeedback therapy, 38 (3) a cognitive behavioral approach to decondition the pathological residual apprehension by highlighting to the patients that residual micromotion does not necessarily lead to recurrent instability, 39 and finally with (4) a rotator cuff reinforcement to avoid further dysfunction due to muscle fatigue.…”
Section: Surgical Techniquementioning
confidence: 99%